The origin and migration of primordial germ cells in sturgeons - Saito, Taiju; Pšenička, Martin; Goto, Rie; Adachi, Shinji; Inoue, Kunio; Arai, Katsutoshi; Yamaha, Etsuro (PloS one, 2014)
Primordial germ cells (PGCs) arise elsewhere in the embryo and migrate into developing gonadal ridges during embryonic development. In several model animals, formation and migration patterns of PGCs have been studied, and it is known that these patterns vary. Sturgeons (genus Acipenser) have great potential for comparative and evolutionary studies of development. Sturgeons belong to the super class Actinoptergii, and their developmental pattern is similar to that of amphibians, although their phylogenetic position is an out-group to teleost fishes. Here, we reveal an injection technique for sturgeon eggs allowing visualization of germplasm and PGCs. Using this technique, we demonstrate that the PGCs are generated at the vegetal pole of the egg and they migrate on the yolky cell mass toward the gonadal ridge. We also provide evidence showing that PGCs are specified by inheritance of maternally supplied germplasm. Furthermore, we demonstrate that the migratory mechanism is well-conserved between sturgeon and other remotely related teleosts, such as goldfish, by a single PGCs transplantation (SPT) assay. The mode of PGCs specification in sturgeon is similar to that of anurans, but the migration pattern resembles that of teleosts.
Keywords: pohyb buněk; ryby; embryonální vývoj; Embryo, Nonmammalian; Cell Movement; Embryonic Development; Fishes; Male; zárodečné buňky; Germ Cells; Animals; embryo nesavčí; mužské pohlaví; ženské pohlaví; biologické modely; Female; zvířata; Models, Biological